Measurement of Coherence Bandwidth in UHF Radio Channels for Narrowband Networks - Jaroslaw Sadowski (International Journal of Antennas and Propagation)
This paper presents results of investigation on the coherence bandwidth of narrowband radio channels in 430 MHz band. The coherence bandwidth values were estimated from a power delay profile obtained by recording CDMA2000 forward channel signals during real-field measurements in various environments: medium city, flat terrain, and hilly terrain in northern Poland. The results of measurements are compared with characteristic parameters of UHF radio channel models defined for exemplary narrowband digital system from the TETRA standard. In all of the tested environments, the coherence bandwidth values during most of an observation time were much higher than 25 kHz. Therefore, the fading in tested UHF narrowband channels should be classified as flat fading.